An Exploration of Individuals' Basic Assumptions towards Self- Resilience after the Covid-19 Pandemic in Aceh Province - Fadhli, Teuku; Situmorang, Dominikus David Biondi; Nurbaity, Nurbaity (COUNS-EDU: The International Journal of Counseling and Education, 2023)
This study aims to look at the basic assumptions of individuals towards self-resilience after trauma due to the COVID-19 Pandemic, this study uses an e-research research method by distributing CBI questionnaires from google form through social media in order to obtain relevant information from various random respondents. While the data analysis technique was carried out by frequency distribution analysis to get the average percentage value of the research results. After analysing the percentage, it was found that the basic assumptions of individuals towards self-resilience after the COVID-19 pandemic with an average percentage of 7.73% VU, 7.720 NS, 18.33 NQR, 34.22% AP, and 32.43% VS. So the results of this study indicate that positive post-traumatic changes towards individual resilience due to the COVID-19 Pandemic occur very realistic changes, where individual resilience can be categorised as very transformational, where individual changes and mental development are much better than the pre-trauma situation before the COVID-19 Pandemic occurred.